(a3)m = a9
⇒ a3m = a9
(∵ if ‘a’ is a real no. and m, n are integers, then (am)n = amn)
⇒ 3m = 9 (∵ base is same)
⇒ m = 3
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
RELATED QUESTIONS :